A Comparison Study of Performance Efficiency of Lead-Acid Batteries Available in the Iraqi Markets. - H. Hamed, Hussein; H. Zainulabdeen, Iman; Sh. Raheem, Samko; E. Mohammed, Awad (International Journal of Engineering and Technology, 2018)
Batteries consider the major important devices for energy storage based on converting the chemical energy to electrical energy. Different types of batteries are available working in different efficiencies. In this work the performance efficiency of five types of batteries available in the Iraqi were assessed. Different operating variables such as Battery Type (Akko, Raggie, Aswar, Terminator, and Hongdeng), Temperature (20, 25, 35, 45, 55, and 65ËšC), and Charging Time (24, 48, and 72 hr) were studied the impact of these on the performance efficiency of each battery type. According to the results obtained in this study, maximum performance efficiency achieved was 7.2 V at optimum operating variables are (temperature 20ËšC), and (charging time 48 hr). Furthermore, a computer was used with Data Logger to be connected with batteries. Finally, the most stable type and resistance to operating conditions was Aswar type in the first rank and Hongdeng type in the last rank.Â Â